AN APPLICATION OF CHORAL READING STRATEGY IN ENGLISH LANGUAGE LESSONS IN ECONOMIC TEXT TO INCREASING READING SKILLS FOR THE STUDENT GRADE XI STATE VOCATIONAL SCHOOL 2 MEDAN - Sarah Nasution; Mierna Zulkarnain; Suhariyanti Suhariyanti (Universitas Dharmawangsa Medan, 2021)
The aims of this study are: (1) to determine the application of Choral Reading learning strategies related to texts related to Economics in learning English; (2) to determine the effectiveness of the implementation of choral reading learning strategies in learning English on students' reading skills. This type of research is Classroom Action Research which consists of two cycles. The subjects in this study were students of class XI, totaling 30 students. Data collection techniques that will be used are observation, documentation, and tests. The technique of qualitative data analysis is to make notes of reflection, thoughts that arise when observing and are the result of the process of comparing, relating, or associating the data displayed with previous data. The results of this class action research showed an increase in initial ability compared to cycle 1, namely students who completed cycle 1 amounted to 15 students or 50.00%. From the results of the second cycle, it can be written that the students who completed were 24 students out of 30 students or 80.00%. From cycle 1 to cycle 2 there was an increase of 30%. This proves that the use of Choral Reading learning strategies is very effectiveKeywords: Reading Skills, Choral Reading Strategy, Classroom Action Research